Epigenetic embedding of childhood adversity: mitochondrial metabolism and neurobiology of stress-related CNS diseases - Bigio, Benedetta; Sagi, Yotam; Barnhill, Olivia; Dobbin, Josh; El Shahawy, Omar; de Angelis, Paolo; Nasca, Carla (Frontiers in Molecular Neuroscience, 2023)
This invited article ad memoriam of Bruce McEwen discusses emerging epigenetic mechanisms underlying the long and winding road from adverse childhood experiences to adult physiology and brain functions. The conceptual framework that we pursue suggest multidimensional biological pathways for the rapid regulation of neuroplasticity that utilize rapid non-genomic mechanisms of epigenetic regulation of gene expression and modulation of metabolic function via mitochondrial metabolism. The current article also highlights how applying computational tools in this time of enormous technological advance in so many aspects of neuroscience and medicine can foster the translation of basic neuroscience discoveries for the development of novel treatment models for mental illnesses, such as depression ultimately to slow the clinical manifestation of Alzheimer’s disease. Citing an expression that many of us heard from Bruce, while “It is not possible to roll back the clock”, deeper understanding of the biological pathways and mechanisms through which stress produces a lifelong vulnerability to altered mitochondrial metabolism can provide a path for compensatory neuroplasticity. The newest findings emerging from this mechanistic framework are among the latest topics we had the good fortune to discuss with Bruce the day before his sudden illness when walking to a restaurant in a surprisingly warm evening that preluded the snowstorm on December 18th, 2019. With this article, we wish to celebrate Bruce’s untouched love for Neuroscience.